2015
DOI: 10.1128/jb.02485-14
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Decoding Fidelity by Ribosomal Proteins S4 and S5

Abstract: bRibosomal proteins S4 and S5 participate in the decoding and assembly processes on the ribosome and the interaction with specific antibiotic inhibitors of translation. Many of the characterized mutations affecting these proteins decrease the accuracy of translation, leading to a ribosomal-ambiguity phenotype. Structural analyses of ribosomal complexes indicate that the tRNA selection pathway involves a transition between the closed and open conformations of the 30S ribosomal subunit and requires disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…Mutagenesis of the rpsE gene was facilitated by the use of a strain carrying a kanamycin resistance cassette downstream of the rpsE coding region, as described previously (11). The GGT glycine codon corresponding to Gly27 in protein uS5 was targeted for mutagenesis in two separate experiments with two different oligonucleotides.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutagenesis of the rpsE gene was facilitated by the use of a strain carrying a kanamycin resistance cassette downstream of the rpsE coding region, as described previously (11). The GGT glycine codon corresponding to Gly27 in protein uS5 was targeted for mutagenesis in two separate experiments with two different oligonucleotides.…”
Section: Methodsmentioning
confidence: 99%
“…␤-Galactosidase assays were carried out on permeabilized, logarithmically growing cells, and activity was expressed in Miller units (11,45). Luciferase assays to test for missense errors were performed using the Dual-Luciferase Reporter assay system from Promega, and luminescence was measured with a GloMax 20/20 luminometer according to the manufacturers' instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the h12/S4/S5 region, which lies on the solvent side of the subunit at an interface between the shoulder subdomain and the remainder of the subunit; h16, which represents the "top" of the shoulder; and h8/h14/L19; elements which contribute to intersubunit bridge B8 (Maisnier-Patin et al 2002McClory et al 2010). A recent reevaluation of S4/S5 mutations showed that all C-terminal truncations of S4 confer a ram phenotype (Agarwal et al 2015). These truncations undoubtedly destabilize the open conformation of the subunit, lending strong support to the idea that domain closure contributes to GTPase activation (Ogle and Ramakrishnan 2005;Voorhees et al 2010;Fredrick 2015).…”
Section: +mentioning
confidence: 99%
“…In this issue, Agarwal and coworkers (27) describe the results of a direct screen for S4-S5 mutations that alter translation fidelity in E. coli. Using a single-step recombineering approach, they mutagenized each gene specifically and screened for those mutations that increase or decrease miscoding.…”
mentioning
confidence: 99%